Pedagogical Continuity of Teacher Training in Tierra del Fuego, Antarctica and South Atlantic Islands, in Times of Pandemic by Covid-19 - Abendaño López, Sandra (Servicio de Publicaciones de la Universidad Pontificia de Salamanca, 2021)
This article aims to present partial results of the PhD thesis “The configuration of the teacher training system of Tierra del Fuego, Antarctica and theSouth Atlantic Islands (AeIAS) from provincialization in 1991 to 2020”, focusing on the problem of the pedagogical continuity of teacher training of Tierra del Fuego, AeIAS, in times of pandemic by Covid-19. Based on the analysis and triangulation of individual interviews, focus groups, institutional projects for pedagogical continuity, national and provincial regulations, the aim is to describe how the training system faced and faced the pandemic situation in order to respond to the pedagogical continuity of provincial teacher training. The results point to the hard work of all the institutional actors who report on the capacity installed in the training system that enabled it to reorganize itself in order to provide appropriate responses to the students undergoing training. El presente artículo tiene como finalidad presentar resultados parciales de la Tesis de Doctorado “La configuración del sistema de formación docentede Tierra del Fuego, Antártida e Islas del Atlántico Sur (AeIAS) desde la provincialización en 1991 hasta 2020”, focalizando en la problemática de la continuidad pedagógica de la formación docente de Tierra del Fuego, AeIAS, en tiempos de pandemia por Covid-19. A partir del análisis y triangulación de entrevistas individuales, grupos focales, proyectos institucionales de continuidad pedagógica, normativa nacional y provincial se pretende describir cómo el sistema formador enfrentó y afrontó la situación de pandemia para dar respuesta a la continuidad pedagógica de la formación docente provincial. Los resultados remiten a un arduo trabajo por parte de todos los actores institucionales que dan cuenta de la capacidad instalada en el sistema formador que le permitió reorganizarse en pos de dar respuestas ajustadas a los estudiantes en formación.